Untargeted Metabolomic Study of Patients with Macular Edema Secondary to Retinal Vein Occlusion in Aqueous Humor - Wei Q; Luo L; Min Y; Gong Y; Wang L (Clinical Ophthalmology)
Qingquan Wei, Liying Luo, Yingjun Min, Yingying Gong, Li Wang Department of Ophthalmology, Tong Ren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Li Wang, Department of Ophthalmology, Tong Ren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China, Email WL1249@shtrhospital.comPurpose: The aim of this study was to identify metabolic biomarkers and investigate the metabolic changes associated with aqueous humor in retinal vein occlusion macular edema (RVO-ME).Methods: Aqueous humor (AH) samples were collected from patients, including those diagnosed with central retinal vein occlusion macular edema (CRVO-ME), branch retinal vein occlusion macular edema (BRVO-ME), and a control group undergoing cataract surgery. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was utilized to analyze the metabolomic profiles in aqueous humor.Results: A total of 28 metabolites were identified as potential biomarkers capable of distinguishing RVO-ME patients from the control group. Of these, 26 metabolites were specific for distinguishing CRVO-ME patients from controls, and 24 metabolites were specific for differentiating BRVO-ME patients from controls. Additionally, 9 metabolites were identified that could differentiate CRVO-ME patients from BRVO-ME patients.Conclusion: This study successfully identified significant metabolic biomarkers that enhance our understanding of the pathogenesis of RVO-ME. These findings may offer new avenues for the treatment of RVO-ME and aid in differentiating between CRVO-ME and BRVO-ME patients.Keywords: metabolomic, retinal vein occlusion, macular edema, aqueous humor